2021
DOI: 10.1016/j.cub.2021.07.038
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary emergence of land plants

Abstract: There can be no doubt that early land plant evolution transformed the planet but, until recently, how and when this was achieved was unclear. Coincidence in the first appearance of land plant fossils and formative shifts in atmospheric oxygen and CO 2 are an artefact of the paucity of earlier terrestrial rocks. Disentangling the timing of land plant bodyplan assembly and its impact on global biogeochemical cycles has been precluded by uncertainty concerning the relationships of bryophytes to one another and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 172 publications
(231 reference statements)
2
48
0
Order By: Relevance
“…These analyses of individual gene families corroborated the pattern of loss along the branch leading to bryophytes. The loss of these orthologous gene families strengthens the hypothesis that ancestral embryophyte had a more complex vasculature system than that of extant bryophytes (Donoghue et al, 2021). Overall, the loss of gene families (Fig.…”
Section: Gene Content Of the Embryophyte Common Ancestorsupporting
confidence: 71%
See 2 more Smart Citations
“…These analyses of individual gene families corroborated the pattern of loss along the branch leading to bryophytes. The loss of these orthologous gene families strengthens the hypothesis that ancestral embryophyte had a more complex vasculature system than that of extant bryophytes (Donoghue et al, 2021). Overall, the loss of gene families (Fig.…”
Section: Gene Content Of the Embryophyte Common Ancestorsupporting
confidence: 71%
“…Likewise, interpretations of the early land plant fossil record have been contingent on the first land plants appearing more like extant bryophytes than tracheophytes. That the ancestral embryophyte may have been more complex than living bryophytes is in keeping with many early macrofossils being both more complex than bryophytes and possessing a mosaic of tracheophyte and bryophyte traits (Edwards et al, 2014;Donoghue et al, 2021). Supplementary Figure 11.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Early cladistic studies using morphological and biochemical characters, as well as the mitochondrial multigene data, strongly supported the paraphyly hypothesis of bryophytes (Mishler and Churchill, 1985; Qiu et al, 2006; Qiu, 2008). The availability of large‐scale nuclear genes and application of more complex evolutionary models have shown that bryophytes formed a monophyletic group, sister to the vascular plants (Figure 2; Puttick et al, 2018; de Sousa et al, 2019; Su et al, 2021; Donoghue et al, 2021). The inconsistent relationships within bryophytes phylogeny is likely caused by lineage‐specific differences of rate variation and deviating amino acid/nucleotide composition.…”
Section: Streptophyte Algae and The Origin Of Land Plantsmentioning
confidence: 99%
“…These adaptions to the environment primarily rely on a regulatory system of phytohormones [ 1 , 2 ]. From the terrestrial colonization by plants in the Paleozoic to the eventual dominance of angiosperms, the phytohormone regulation systems have continuously evolved, forming various regulation networks [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%